A Review of Animal Models of Intervertebral Disc Degeneration: Pathophysiology, Regeneration, and Translation to the Clinic. (22nd May 2016) - Daly, Chris; Ghosh, Peter; Jenkin, Graham; Oehme, David; Goldschlager, Tony
Abstract : Lower back pain is the leading cause of disability worldwide. Discogenic pain secondary to intervertebral disc degeneration is a significant cause of low back pain. Disc degeneration is a complex multifactorial process. Animal models are essential to furthering understanding of the degenerative process and testing potential therapies. The adult human lumbar intervertebral disc is characterized by the loss of notochordal cells, relatively large size, essentially avascular nature, and exposure to biomechanical stresses influenced by bipedalism. Animal models are compared with regard to the above characteristics. Numerous methods of inducing disc degeneration are reported. Broadly these can be considered under the categories of spontaneous degeneration, mechanical and structural models. The purpose of such animal models is to further our understanding and, ultimately, improve treatment of disc degeneration. The role of animal models of disc degeneration in translational research leading to clinical trials of novel cellular therapies is explored.